2022
DOI: 10.1029/2022jg006903
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic and Terrestrial Plant Contributions to Sedimentary Plant Waxes in a Modern Arctic Lake Setting

Abstract: The Arctic is the fastest-warming region on Earth, with mean annual temperatures expected to increase 10°C by the end of the century under the most extreme scenarios (IPCC, 2021). Arctic precipitation is also expected to increase as local evaporation from newly ice-free seas and poleward moisture transport increase (Bintanja & Andry, 2017) (Singh et al., 2017). This rapid climate change is exacerbated by positive feedbacks primarily linked to decreasing albedo (Holland & Bitz, 2003). Records of past Arctic cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 73 publications
(135 reference statements)
2
17
0
Order By: Relevance
“…The lower εapp values in aquatic plants compared to angiosperms and gymnosperms is consistent with previous findings (Chikaraishi and Naraoka, 2003;Duan et al, 2014;Aichner et al, 2017;Dion-Kirschner et al, 2020). Mosses are another possible contributor to the sedimentary n-C23 pool as they have been shown to primarily synthesize mid-chain n-alkanes (Sachse et al, 2006;Nichols et al, 2009;Bush and McInerney, 2013;Hollister et al, 2022). Although we did not sample mosses in this study, moss εC39/MAP values have been shown to be more positive than those of terrestrial plants (Sachse et al, 2006).…”
Section: Provenance Of Mid-and Long-chain N-alkanes In Sedimentary Ar...supporting
confidence: 90%
“…The lower εapp values in aquatic plants compared to angiosperms and gymnosperms is consistent with previous findings (Chikaraishi and Naraoka, 2003;Duan et al, 2014;Aichner et al, 2017;Dion-Kirschner et al, 2020). Mosses are another possible contributor to the sedimentary n-C23 pool as they have been shown to primarily synthesize mid-chain n-alkanes (Sachse et al, 2006;Nichols et al, 2009;Bush and McInerney, 2013;Hollister et al, 2022). Although we did not sample mosses in this study, moss εC39/MAP values have been shown to be more positive than those of terrestrial plants (Sachse et al, 2006).…”
Section: Provenance Of Mid-and Long-chain N-alkanes In Sedimentary Ar...supporting
confidence: 90%
“…The contrasting results from Hollister et al (2022) and Dion-Kirschner et al (2020) highlight the variability of plant wax production, transport, and deposition in high latitude lakes. Continued efforts to fingerprint the sources n-alkyl compounds, and to build a mechanistic understanding of biomarker and isotope systematics, will support applications of the dual-biomarker isotope method for reconstructing past changes in Arctic humidity and precipitation seasonality.…”
Section: Future Opportunitiesmentioning
confidence: 92%
“…The contrasting results from Hollister et al. (2022) and Dion‐Kirschner et al. (2020) highlight the variability of plant wax production, transport, and deposition in high latitude lakes.…”
Section: Future Opportunitiesmentioning
confidence: 96%
See 2 more Smart Citations